2019
DOI: 10.1111/acel.13025
|View full text |Cite
|
Sign up to set email alerts
|

Aging‐related carcinoembryonic antigen‐related cell adhesion molecule 1 signaling promotes vascular dysfunction

Abstract: Aging is an independent risk factor for cardiovascular diseases and therefore of particular interest for the prevention of cardiovascular events. However, the mechanisms underlying vascular aging are not well understood. Since carcinoembryonic antigen‐related cell adhesion molecule 1 (CEACAM1) is crucially involved in vascular homeostasis, we sought to identify the role of CEACAM1 in vascular aging. Using human internal thoracic artery and murine aorta, we show that CEACAM1 is upregulated in the course of vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 48 publications
(94 reference statements)
0
19
1
Order By: Relevance
“…However, the main function of HIF-1α is the inhibition of the proliferation and migration of human VSMCs, indicating that HIF-1α induces VSMC phenotype switching [150]. However, stabilization of the HIF-1α protein in 9-month-old WT mice promoted increased endothelial permeability [152].…”
Section: Hif and Vascular Smooth Muscle Cellsmentioning
confidence: 99%
“…However, the main function of HIF-1α is the inhibition of the proliferation and migration of human VSMCs, indicating that HIF-1α induces VSMC phenotype switching [150]. However, stabilization of the HIF-1α protein in 9-month-old WT mice promoted increased endothelial permeability [152].…”
Section: Hif and Vascular Smooth Muscle Cellsmentioning
confidence: 99%
“…A hallmark of vascular aging is the increased deposition of collagen fibers within the media of larger vessels. Intriguingly, we found that only in the presence of CEACAM1 vascular aging in mice was accompanied by vascular fibrosis presumably due to enhanced TGFβ/TGF-βR1 signaling whereas genetic deletion of CEACAM1 completely prevented aortic collagen accumulation [1]. Our in vitro data suggest that CEACAM1 modulates endothelial TGF-β/TGF-βR1 signaling in a TNF-α-dependent manner [1].…”
Section: Editorialmentioning
confidence: 74%
“…Since we showed previously that CEACAM1 is critically involved in TNF-α-mediated endothelial barrier breakdown via adherens junction disassembly [3], we wondered whether CEACAM1 might also contribute to vascular aging. As a first hint, we observed re-expression of CEACAM1 in the murine and human vasculature with progressive age [1]. This upregulation of vascular CEACAM1 expression is of great importance since we demonstrated that the presence of CEACAM1 is necessary for age-associated vascular upregulation of TNF-α using a murine CEACAM1 knockout model.…”
mentioning
confidence: 66%
See 2 more Smart Citations